A Professor's Theory and It's Practical Uses: The Work of J. Willard Gibbs & Some Applications to Industry - Yale University (Yale University Press, 1939)
Booklet created to celebrate the 100th anniversary of the birth of Josiah Willard Gibbs (1839-1903). Gibbs, a Yale alumnus, was an American chemist and pioneer in the field of physical chemistry.
Keywords: Gibbs, J. Willard (Josiah Willard), 1839-1903; Chemists; Chemistry, Physical and theoretical; Biographies; Yale University